Images of God in Toba Batak storytelling - Angerler, Johann (Wacana, Journal of the Humanities of Indonesia, 2016)
This paper examines the ways in which God the Creator, the High God, is described in Toba Batak folk-tales. The sources for this investigation are stories recorded in pre-colonial (around 1850), colonial and post-colonial times (up to 2014). In different stories the High God can appear under various names, forms and gender, and resides in various places never inhabited by humans. Unlike a Deus otiosus, the Toba Batak High God is not "inactive" after creation, but continues to be involved in the life of mankind through local or supra-local manifestations. Although he rules the realm of death, he is nevertheless regarded as the source of life, fertility, health and prosperity. There are also stories about manifestations of God in which he shares the experience of suffering with human beings. The main Toba Batak community rituals in pre-colonial times were addressed to a manifestation of the High God.